2019
DOI: 10.22146/jsv.42944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pengobatan Trematodiasis Menggunakan Albendazol pada Sapi di Kecamatan Pakem, Sleman, Daerah Istimewa Yogyakarta

Abstract: The recent method of treatment for trematodiasis in cattle (age 1-10 years) using albendazol (10% of orally suspension) has deducted to evaluate the effectiveness of this anthelmintic to eradicate the trematoda infection especially Fasciola sp. and Paramphistomum sp. in Pakem subdistrict, Sleman district, Daerah Istimewa Yogyakarta Provence. These two species of trematodes were the mostly found in Yogyakarta area according to the annualy reports of Idul Qurban slaughter day. The cows used in this study were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…Albendazole has an excellent ability to kill adult worms with an effectiveness of up to 75%. Albendazole also can reduce the number of worm eggs in the infected host [32]. Kay et al [33] asserted that albendazole works by binding to beta-tubulin at the colchicine-sensitive site of the cell wall.…”
Section: Tannins Positive Formation Of Dark Green Colormentioning
confidence: 99%
“…Albendazole has an excellent ability to kill adult worms with an effectiveness of up to 75%. Albendazole also can reduce the number of worm eggs in the infected host [32]. Kay et al [33] asserted that albendazole works by binding to beta-tubulin at the colchicine-sensitive site of the cell wall.…”
Section: Tannins Positive Formation Of Dark Green Colormentioning
confidence: 99%
“…Ke gagalan terapi flukisidal sintetik termasuk Albendazol akibat resistensi telah dilaporkan dalam studi (Novobilsky dan Höglund, 2015). Efikasi Albendazol 10 mg/kg BB pada sapi fasciolosis di daerah Sleman menurun hingga 30% menimbulkan dugaan resistensi (Kristiyani, et al, 2019).…”
Section: Pendahuluanunclassified
“…Several studies have reported resistance to the use of synthetic anthelmintic including Albendazole due to frequent and inappropriate use [14]. Medicinal plants can be used as an alternative to overcome the limitations of synthetic anthelmintics.…”
Section: Introductionmentioning
confidence: 99%